The Efforts of Lifelong Education through Life Skills for Early Childhood in Play Groups - All Fine Loretha; Mintarsih Arbarini; Liliek Desmawati; Felestin Felestin (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
Education has a vital role in stimulating the growth and development of children. Currently, education is only focused on achieving cognitive outcomes, even though children need to be able to help themselves and become empowered for their lives in lifelong through life skills. This study described efforts to implement lifelong education by training life skills in early childhood in playgroups and its impacts. The method used is a case study with a qualitative approach. The subjects of this study were six teachers, four parents, and two students involving two playgroups. The stages of analysis data include data collection, reduction, and conclusion. The implementation of lifelong education in playgroups is carried out by providing stimulus regarding activities that trigger the growth of life skills for early childhood. Life skills in playgroups are applied through life skills centers. Life skills include social life, responsibility, self-awareness, gender awareness, decision-making, survival, and self-care. Activities related to life skills stimulate children’s lifelong learning. This research can be a reference for early childhood teachers to facilitate children learning through life skills for lifelong education.